Faktor-Faktor yang Mempengaruhi Return On Assets (ROA) - Priyanto, Aria Aji (Universitas muhammadiyah palembang, 2019)
This research aims to examine the factors which affect Return on Asset consists of Cash Turnover and Receivables Turnover at Manufacture Companies on PT. Indocement Tunggal Prakarsa,Tbk. in 2007-2017.This research is causality using quantitative approach. Variables used are three variables, those are independent variables which Cash Turnover (X1) and Receivables Turnover (X2) with dependent variables is Return On Asset (Y). The population in this research includes manufacturing companies sub-sector of cement. The sample used in this research is PT. Indocement Tunggal Prakarsa Tbk. Year 2007 until 2017. The analytical tool used is multiple linear regression.According to the research result, find: (1) Cash Turnover and Receivables Turnover simultaneously have positive and significant effects to Return On Asset on PT. Indocement Tunggal Prakarsa, Tbk. and (2) Cash Turnover and Receivables Turnover partially have positive and significant effects to Return On Asset on PT. Indocement Tunggal Prakarsa, Tbk.